REALITAS PENYIMPANGAN SOSIAL DALAM KONTEKS CYBER SEXUAL HARRASMENT PADA JEJARING SOSIAL LIVE STREAMING BIGO LIVE - Abdul Munir; Riki Harianto (UIR PRESS, 2019)
live streaming is a latest innovation for people to express themselves and exchange ideas. The current social media that is becoming a trend among the people and using live streaming as a means to interact is social media live streaming Bigo live. The existence of bigo live as an internet community forum (Cyber Community) certainly changes in the norms and values ​​adopted by these users, so it cannot be denied that in the internet community (Cyber Community) there are changes and rules that occur . One of them appears an interaction created virtually in the world, where the emergence of a form of deviation that occurs in social media live streaming bigo live, one of which is cyber sexual harassment. The method used in this study uses visual methods. The theory used in this paper is the theory of routine activities where observations take place and observe every bigo live social media user.